Study of an Analytical Model that represent Student Loyalty: Case Study of a Private University in Peru - Carhuancho-Mendoza, Irma Milagros (2023)
Student loyalty was explained based on multiple factors and variables such as institutional image, educational quality, academic fees, and educational service in a Peruvian university that provides educational service, both at undergraduate and graduate levels. The non-experimental research investigated theoretical models to understand student loyalty from four variables. It was evidenced that educational quality and institutional image were key factors to generate loyalty in students towards their educational institution. On the other hand, although the academic fee is considered by students when choosing a university, it was not shown that it is linked to generating student loyalty, which highlights the importance of evaluating other aspects such as educational service and institutional reputation. It was highlighted that Peruvian universities need to plan and implement quality standards and develop a solid and favorable image to encourage student permanence.